Effects of different monochromatic lights on umami and aroma of dried Suillus granulatus. (15th March 2023) - Feng, Yao; Xu, Heran; Fan, Yiming; Ma, Fengming; Du, Bin; Li, Yunting; Xia, Rongrong; Hou, Zhenshan; Xin, Guang
Highlights: Blue-light was better for improving the umami and aroma of dried S. granulatus. The lowest umami and aroma were in red-light and in green-light respectively. Umami and aroma in five light treatments were better at 6 and 9 days. Glu, Asp, alcohols, ketones and pyrazines contributed to flavor differences under different light treatments. Abstract: Dried edible mushrooms have a unique flavor which is worth exploring to preserve and improve their flavor. Light can improve flavor for dried edible mushrooms, but there are few reports about monochromatic light. In this study, effects of red-light, yellow-light, green-light, blue-light and white-light on the umami taste and aroma of dried Suillus granulatus were investigated. The results showed that contents of umami amino acids and 5-nucleotides, equivalent umami concentration (EUC) and electronic tongue umami scores were higher under blue-light treatment. Principal component analysis (PCA) of volatiles showed that comprehensive scores under blue-light treatment were higher. The flavor was better under five light treatments at 6 and 9 days. Partial least squares-discrimination analysis (PLS-DA) further revealed the detailed differences between various light treatments, which were mainly caused by umami amino acids, alcohols, ketones and pyrazines. Collectively,  blue-light treatment can be used as a processing technology to improve the flavor quality of dried edible mushrooms.